Prospects and challenges of nanomaterials in sustainable food preservation and packaging: a review - Ritesh Pattnaik; Sandeep Kumar Panda; Soumyadeep Biswas; Sayanti De; Subhra Satahrada; Subrat Kumar (Discover Nano)
Abstract Nanomaterials play a pivotal role in food preservation and its safety, offering ingenious solutions for sustainable food packaging. Nanomaterials enable the creation of packaging materials having unique functional properties. It not only extends the shelf life of the foods by releasing preservatives but also enhances food safety by preventing microbial contamination or food spoilage. In this review, we aim to provide an overview of the various applications of nanotechnology in food packaging, highlighting its key advantages. We also delve into the safety considerations and regulatory issues involved in developing nanotechnology-based food packaging materials. Additionally, advancements in the field of nanotechnology-based packaging have the potential to create safer, more sustainable, and high-quality packaging with greater functionality that delivers essential benefits to manufacturers and consumers.